Solitary, reproductive, and parental behavior of maned wolves (Chrysocyon brachyurus) - Bestelmeyer, Stephanie V., author; Herbers, Joan M., advisor; Andelt, William F., committee member; Nash, Donald J., committee member; Reading, Richard, committee member (Colorado State University. Libraries, 2000)
The maned wolf is an endangered species native to central South America. Efforts to preserve the species in the wild and through captive breeding programs have been hampered by a lack of information on its natural history. The maned wolf is a member of the family Canidae, which is known for extensive paternal care. Thus, the maned wolf is an interesting species for studying parental investment theory. I studied maned wolves in U.S. zoos and in Emas National Park, Brazil to gather information necessary for developing conservation plans while simultaneously testing many parental care theories. High pup mortality, often caused by females abandoning or cannibalizing newborns, plagued early captive breeding efforts. At the time, the custom at most zoos was to remove the male prior to birth for fear that he would harm pups or that his presence would stress the female, causing her to harm pups. I compared pup survival in the presence and absence of males and found that male care increased pup survival, as predicted by the paternal investment hypothesis. I observed seven pairs to test predictions arising from game theory models of parental investment and suggest that increased pup survival is due, in part, to decreased aggression by females to pups when males are present. Furthermore. I outlined a procedure to reintroduce males to their pups if they have been removed prior to birth. Estrous timing in seasonal mammals can be triggered by a variety of cues, and I showed that maned wolf estrus is influenced more by internal factors than by temperature or latitude. During 1997, I studied the behavior of habituated, free-ranging maned wolves and provided new information on their solitary, hunting, marking, parental, and social behavior. Finally, I compared the behavior of free-ranging and captive maned wolves and showed that generalizing from captive animals to their free-ranging counterparts may not be appropriate.
Keywords: ecology; zoology; forestry